Pengaruh Terapi Progressive Muscle Relaxation Terhadap Tingkat Kecemasan Mahasiswa Keperawatan Selama Pandemi Covid-19 Di Universitas Nasional - Rahma Hanifah; Nita Sukamti; Andi Mayasari Usman (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Severe acute respiratory syndrome coronavirus (SARS-CoV-2) or Covid-19 is a virus that attacks the respiratory system. The spread of the Covid-19 virus is very fast and wide so it has changed several orders of people's lives from economic, social, and educational. Interview results were obtained during the Covid-19 pandemic, one of the respondents' anxiety factors was the implementation of distance lectures which could usually be done face-to-face. Anxiety is an uneasy feeling like worry and fear. There are several ways to overcome anxiety levels, namely pharmacological therapy and non-pharmacological therapy, one of which is Progressive Muscle Relaxation therapy. Progressive Muscle Relaxation Therapy is a therapy that involves the contraction and relaxation of various muscle groups from the feet to the head downwards. This study aims to determine the effect of Progressive Muscle Relaxation therapy to reduce anxiety levels of nursing students at the National University. This quasi-experimental study used a one-group pretest and posttest. The sample in this study amounted to 44 nursing students. The sampling technique used the purposive sampling technique. The research instrument used the Hamilton Rating Scale of Anxiety (HRS-A) anxiety level questionnaire. This questionnaire has been tested for validity and reliability internationally. The data were analyzed using descriptive statistics, namely Wilcoxon to determine the difference in anxiety level scores in one group. The results showed that there was a significant difference in behavioral scores before and after being given Progressive Muscle Relaxation therapy with a p-value = 0.000 <0.05. Progressive Muscle Relaxation Therapy can reduce the anxiety level of nursing students. Keywords: Anxiety Level, Progressive Muscle Relaxation, Pandemic Covid-19, Nursing Students    ABSTRAK Severe acute respiratory syndrome coronavirus (SARS-CoV-2) atau Covid-19 adalah virus yang menyerang sistem pernapasan. Penyebaran virus Covid-19 sangat cepat dan luas sehingga telah merubah beberapa tatanan kehidupan masyarakat dari mulai ekonomi, social, dan pendidikan. Didapatkan hasil wawancara selama pandemic Covid-19 salah satu faktor kecemasan responden adalah karena diberlakukannya perkuliahan jarak jauh yang biasanya bisa dilakukan secara tatap muka. Kecemasan adalah perasaan yang tidak mudah seperti khawatir dan takut. ada beberapa cara untuk mengatasi tingkat kecemasan yaitu terapi farmakologi dan terapi non farmakologi salah satunya yaitu terapi Progressive Muscle Relaxation. Terapi Progressive Muscle Relaxation merupakan terapi yang melibatkan kontraksi dan relaksasi berbagai kelompok otot mulai dari kaki sampai kepala kearah bawah. Penelitian ini bertujuan untuk mengetahui pengaruh terapi Progressive Muscle Relaxation untuk menurunkan tingkat kecemasan mahasiswa keperawatan di Universitas Nasional. Penelitian quasi-experiment ini menggunakan rangan one group pretest anad posttest. Sampel dalam penelitian ini berjumlah 44 mahasiswa keperawatan. Teknik pengambilan sampel menggunakan purposive sampling technique. Intrument penelitian menggunakan kuesioner tingkat kecemasan Hamilton Rating Scale of Anxiety (HRS-A) kuesioner ini telah di uji validas dan reabilitasnya secara internasional . data dianalinis menggunakan deskriptif statistic yaitu wilcoxon untuk mengetahui perbedaan skor tingkat kecemasan  dalam satu kelompok. Hasil penelitian menunjukan bahwa ada perbedaan yang signifikan pada skor perilaku sebelum dan sesudah diberikan terapi Progressive Muscle Relaxation dengan nilai p =0.000<0.05. Terapi Progressive Muscle Relaxation mampu menurunkan tingkat kecemasan mahasiswa keperawatan Kata Kunci : Tingkat Kecemasan, Progressive Muscle Relaxation, Pandemi Covid-19,  mahasiswa keperawatan